Sex-Biased Inbreeding Effects on Reproductive Success and Home Range Size of the Critically Endangered Black Rhinoceros - Cain, Bradley; Wandera, Antony B.; Shawcross, Susan G.; Harris, W. Edwin; Stevens-Wood, Barry; Kemp, Stephen J.; Okita-Ouma, Benson; Watts, Phillip C. (Wiley, 2014)
A central premise of conservation biology is that small populations suffer reduced viability through loss of genetic diversity and inbreeding. However, there is little evidence that variation in inbreeding impacts individual reproductive success within remnant populations of threatened taxa, largely due to problems associated with obtaining comprehensive pedigree information to estimate inbreeding. In the critically endangered black rhinoceros, a species that experienced severe demographic reductions, we used model selection to identify factors associated with variation in reproductive success (number of offspring). Factors examined as predictors of reproductive success were age, home range size, number of nearby mates, reserve location, and multilocus heterozygosity (a proxy for inbreeding). Multilocus heterozygosity predicted male reproductive success (p< 0.001, explained deviance >58%) and correlated with male home range size (p < 0.01, r2 > 44%). Such effects were not apparent in females, where reproductive success was determined by age (p < 0.01, explained deviance 34%) as females raise calves alone and choose between, rather than compete for, mates. This first report of a 3‐way association between an individual male's heterozygosity, reproductive output, and territory size in a large vertebrate is consistent with an asymmetry in the level of intrasexual competition and highlights the relevance of sex‐biased inbreeding for the management of many conservation‐priority species. Our results contrast with the idea that wild populations of threatened taxa may possess some inherent difference from most nonthreatened populations that necessitates the use of detailed pedigrees to study inbreeding effects. Despite substantial variance in male reproductive success, the increased fitness of more heterozygous males limits the loss of heterozygosity. Understanding how individual differences in genetic diversity mediate the outcome of intrasexual competition will be essential for effective management, particularly in enclosed populations, where individuals have restricted choice about home range location and where the reproductive impact of translocated animals will depend upon the background distribution in individual heterozygosity.Efectos de la Endogamia Sesgada por el Sexo sobre el Éxito Reproductivo y el Rango del Tamaño de Hábitat del Rinoceronte Negro, Especie en Peligro Crítico